Найпоширеніші загрози безпеці електронній пошті та методи захисту від них - Шевчук, В. В. (ХНУРЕ, 2024)
The most common 2023 attacks are considered and effective methods of protection against them are proposed. Phishing, social engineering, virus attacks, and other forms of cybercrime often attempt to use mail to gain unauthorized access to sensitive information or cause other harmful effects. Therefore, there is a need to effectively protect users and organizations from cyber threats that can lead to large financial losses, violate privacy, and increase malware.
Keywords: електронна пошта; захист електронної пошти